Microbial ecology and biogeochemistry of iron cycling in water columns and sediments of anoxic stratified lakes - (:unkn) unknown (My University, 2025)
Recent models for early earth ocean chemistry suggest that it had progressed from an anoxic, iron-rich state in the Archean to a sulfide-rich state in the late Proterozoic and then, with increasing oxygen concentrations in the atmosphere, into the completely oxic ocean we know today. From the late Archean-early Proterozoic iron-rich (2.2-1.8 Ga = billion years before present) ocean massive deposits of mostly iron oxide minerals precipitated and formed the so called “Banded iron formations”. These BIF deposits are found essentially on all continents, may cover vast areas, and make up more than 90% of the world’s commercial iron supply. The mechanisms of formation of these sediments are still unknown but until recently purely inorganic processes were thought to be responsible. The contribution of microorganisms to ferric iron deposition remained unexplored. Stratified water bodies with sulfidic bottom waters, resembling middle to late Proterozoic ocean, have received considerable attention (e.g. Black Sea, meromictic lakes) and the chemical and microbiological processes in water column and sediments are relatively well known. Results from such studies have been indispensable for the interpretation of the geological record. Yet a modern analogue to an ancient iron-rich ocean from which the massive banded iron formations precipitated, has not been studied so far. Iron-rich but sulfate-poor meromictic lakes may represent such modern analogues but only a few of these lakes are known worldwide. In this project the microbial ecology and the biogeochemical cycles of two of them will be explored by an interdisciplinary approach combining state of the art techniques from microbiology, molecular ecology and biogeochemistry. This research will allow us to test new concepts on ancient ocean productivity and banded iron formation. It may give new insights for researchers working on Archean and early Proterozoic ocean (bio-) geochemistry and will help to understand how the biogeochemical cycles of iron, carbon and other elements were operating at that time.
Keywords: microbial ecology; molecular ecology; bacterial communities; diversity; DGGE; FISH